2020
DOI: 10.1002/ctm2.269
|View full text |Cite
|
Sign up to set email alerts
|

CD73 alleviates GSDMD‐mediated microglia pyroptosis in spinal cord injury through PI3K/AKT/Foxo1 signaling

Abstract: Inflammatory programmed cell death pyroptosis executed by the pore-forming protein gasdermin D (GSDMD) is an essential step of neuroinflammation after spinal cord injury. We demonstrated that CD73, a widely accepted immunosuppressive molecule, can inhibit pyroptosis via mediating GSDMD through PI3K/AKT/Foxo1 signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 69 publications
0
107
0
Order By: Relevance
“…Thus, secondary injury prevention and intervention are considered promising treatments for SCI [ 8 ]. Among the mentioned pathophysiologic events in secondary injury, cell death and inflammation are considered to be two critical targets for SCI treatment [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, secondary injury prevention and intervention are considered promising treatments for SCI [ 8 ]. Among the mentioned pathophysiologic events in secondary injury, cell death and inflammation are considered to be two critical targets for SCI treatment [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the microglia pyroptosis has also emerged as another important resource of neuroin ammation in SCI. In our previous studies, we have identi ed the crucial role of microglia pyroptosis in SCI [15]. It is a novel kind of in ammatory programmed cell death characterized by cell swelling and lysis, leading to the secretion of proin ammatory cytokines (including IL-1β, IL-18 and TNF-α).…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have shown that NLRP3-mediated pyroptosis plays crucial roles in various diseases including intestinal diseases [10], cardiovascular diseases [11,12], neurological disease [13] as well as the age-related diseases [14]. Importantly, some researchers and we previously reported that NLRP3 in ammasome-mediated pyroptosis is also involved in SCI and the inhibition of pyroptosis may be one of the potential treatment targets for SCI [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…During NLRP3 inflammasome activation, ASC and NLRP3 oligomerization are acritical steps for the subsequent caspase‐1 activation. 3 , 4 , 5 , 6 NR4A1 deficiency aggravates Nigericin‐induced amounts of ASC specks, and the interaction between NLRP3 and ASC in BMDMs (Figure 2F and Figure S4 ). Meanwhile, overexpression of NR4A1 inhibits canonical and non‐canonical NLRP3 inflammasome activation in THP‐1 and BMDMs (Figure S2D,G and Figure S3E,F ).…”
Section: Figurementioning
confidence: 98%